Media i usługi biblioteczne dla grup zagrożonych wykluczeniem społecznym = Media and library services for groups at risk of social exclusion - Fedorowicz-Kruszewska, Małgorzata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Polish society is not homogenous. It also includes groups at risk of social exclusion. It is difficult to estimate what percentage of Polish society is excluded, although sociologists indicate that it could be as high as 18%. The phenomenon of social exclusion is diagnosed in all countries, although its causes may be different. Most often, researchers for groups exposed to social exclusion include lonely people, the unemployed, seniors, people with disabilities, persons living in the countryside, those addicted to psychoactive drugs, with low education, in conflict with the law, poor people as well as foreigners, immigrants, and national and ethnic minorities. Libraries have an important role to play in preventing and reducing social exclusion. They are not able to include all groups threatened by social exclusion with their activities, but not everyone expects profiled resources and library services. That is why libraries most often direct their actions to senior citizens, people with disabilities, the unemployed, rural residents, and less frequently to foreigners and national and ethnic minorities. Prevention and minimization of social exclusionis carried out at libraries by purchasing and collecting special document formats, equipping premises with supporting technologies, taking care of the design of available library websites, and, finally, including services prepared for people with specific needs, as well as encouraging anyone who doesn?t require a personalized approach to use their services.
Keywords: wykluczenie społeczne; Inkluzja cyfrowa i społeczna; biblioteka; dostępność; usługi biblioteczne; social exclusion; Social and digital inclusion; library; accessibility; Library services